PENGEMBANGAN INSTRUMEN PENILAIAN PORTOFOLIO BERBASIS KKNI DAN SN-DIKTI UNTUK MENDUKUNG IMPLEMENTASI MBKM: Studi pada Kurikulum Outcome-Based Education Program Studi Pendidikan Vokasional Teknik Mesin Universitas Ivet - Mahendra, M.T., Sena; Suwignyo, Joko; Hafidz, Miftah Al; Bahtiar, Fahmy Zuhda (Journal of Automotive Technology Vocational Education, 2024)
This study aims to develop a portfolio assessment instrument based on the Indonesian National Qualifications Framework (KKNI) and the National Higher Education Standards (SN-DIKTI) to support the implementation of the Merdeka Learning Campus Merdeka (MBKM) program in the Outcome-Based Education (OBE) curriculum. The research subject is the Mechanical Engineering Vocational Education (PVTM) study program at IVET University. The research method uses the 4-D model (Define, Design, Develop, Disseminate), which consists of the stages of needs definition, instrument design, validation, and development. The developed instrument was designed in a five-level Likert scale format, covering three main aspects: cognitive, affective, and psychomotor. The results of validation by experts showed a high level of validity with an average score of 0.85 (very valid). Testing was conducted in the Research Methods course involving 30 students, resulting in an average portfolio assessment score of 78.5 (good). Feedback from lecturers showed that this instrument increased the accuracy of the assessment, while students found the instrument easy to understand and use. Keywords: Portfolio Assessment Instrument, KKKNI, SN-Dikti, MBKM, OBE, Vocational Education, Mechanical Engineering